A novel anti-galectin-9 immunotherapy limits the early progression of pancreatic neoplastic lesions in transgenic mice - Quilbe, Alexandre; Mustapha, Rami; Duchêne, Belinda; Kumar, Abhishek; Werkmeister, Elisabeth; Leteurtre, Emmanuelle; Moralès, Olivier; Jonckheere, Nicolas; Van Seuningen, Isabelle; Delhem, Nadira (Frontiers in Immunology, 2023)
Background: Pancreatic adenocarcinoma (PDAC) is a devastating disease with an urgent need for therapeutic innovation. Immune checkpoint inhibition has shown promise in a variety of solid tumours, but most trials have failed to demonstrate efficacy in PDAC. This is partly explained by a highly immunosuppressive microenvironment, which dampens anti-tumour immunity through the recruitment or induction of regulatory T cells (Tregs). In this context, our laboratory has developed a novel immunotherapeutic strategy aimed at inhibiting the suppressive activity of Tregs, based on a patented (EP3152234B1) monoclonal antibody (mAb) targeting galectin 9 (LGALS9). Material and Methods: CD4+ conventional T cells (TCD4 or Tconv), Treg ratio and LGALS9 expression were analysed by immunohistochemistry (IHC) and cytometry in blood and pancreas of K-rasLSL.G12D/+;Pdx-1-Cre (KC) and K-rasWildType (WT);Pdx1-Cre (WT) mice aged 4 to 13 months. Pancreatic intraepithelial neoplasm (PanIN) progression and grade were quantified using FIJI software and validated by pathologists. The anti-galectin-9 mAb was validated for its use in mice on isolated murine Treg. Its specificity and functionality were validated in proliferation assays on rLGALS9-immunosuppressed murine Tconv and in suppression assays between murine Treg and Tconv. Finally, two months old KC mice were treated with anti-LGALS9 and compared to WT mice for peripheral and infiltrating TCD4, Treg and PanIN progression. Results: IHC and cytometry revealed a significant increase in LGALS9 expression and Treg levels in the blood and pancreas of KC mice proportional to the stages of PanIN. In WT mice, LGALS9 is expressed at a basal level with low and restricted expression, while Treg cells are few in their circulation and even absent from the pancreas. Our anti-LGALS9 mAb used in mice, indicate that murine Treg express LGALS9; the mAb can target and inhibit murine LGALS9 and neutralise Treg suppressive activity. Finally, the anti-LGALS9 mAb in KC mice reduced LGALS9 expression in pancreatic cancer cells, the Treg ratio and the surface area of PanIN. Conclusion: We demonstrate that an anti-LGALS9 mAb, by targeting LGALS9 produced by tumour and Treg, can limit the progression of pancreatic preneoplastic lesions in mice, opening up new prospects for its use as an immunotherapeutic tool in PDAC.